2020
DOI: 10.1002/smll.202003342
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Controllable Synthesis of Nanocrystallized Nickel‐Cobalt Boride Electrode Materials via a Mircoimpinging Stream Reaction for High Performance Supercapacitors

Abstract: Nickel-cobalt borides (denoted as NCBs) have been considered as a promising candidate for aqueous supercapacitors due to their high capacitive performances. However, most reported NCBs are amorphous that results in slow electron transfer and even structure collapse during cycling. In this work, a nanocrystallized NCBs-based supercapacitor is successfully designed via a facile and practical microimpinging stream reactor (MISR) technique, composed of a nanocrystallized NCB core to facilitate the charge transfer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…It is worth mentioning that, specific capacitances can be calculated by various equations as mentioned in the literature in varying unit terms as well, however, recently researchers have initiated to use the equation given below explicitly for nonlinear charge–discharge curves [ 46,47 ] Cnormals= 2imVdt Vnormalf Vnormali2 …”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that, specific capacitances can be calculated by various equations as mentioned in the literature in varying unit terms as well, however, recently researchers have initiated to use the equation given below explicitly for nonlinear charge–discharge curves [ 46,47 ] Cnormals= 2imVdt Vnormalf Vnormali2 …”
Section: Resultsmentioning
confidence: 99%
“…[30] This peak is covered by a broad peak at 3500 cm -1 for Ni 0.85 Co 0.15 (OH) 1.77 Cl 0.23 , ascribing to the -OH bending mode of the enriched interlayer H 2 O. [31,32] Moreover, the peak at 677 cm -1 is the deformation vibration mode of Ni/ Co-OH, [28] which shifts to a lower wavenumber of 617 cm -1 for Ni 0.85 Co 0.15 (OH) 2c). [33] In addition, Ni 0.85 Co 0.15 (OH) 1.77 Cl 0.23 shows a lower mass loss rate at 200-300 °C during the dehydration process and a higher mass retention after 300 °C compared with Ni 0.85 Co 0.15 (OH) 2 , revealing higher thermal stability of Ni 0.85 Co 0.15 (OH) 1.77 Cl 0.23 as a result of Clsubstitution.…”
Section: Resultsmentioning
confidence: 99%
“…The two peaks located at 3440 and 1631 cm −1 can be ascribed to the O-H stretching and bending vibrations of absorbed water within the material skeleton, respectively. It is found that two characteristic peaks appear at 1278 and 1423 cm −1 in NCBO/RGO-3, which indicates the existence of the B-O stretching vibration ( Zhang et al, 2020 ). The infrared peak centered at 1112 cm −1 belongs to the vibration of SO 4 2− residue in NCBO/RGO-3, while the infrared peaks located at 671 and 561 cm −1 are derived from the M-B (M = Co, Ni) bonds between the metal and boron atoms ( Chen et al, 2017b ).…”
Section: Resultsmentioning
confidence: 99%
“…The electron transfer resistances ( R ct ) of NCBO/RGO composites are much smaller than that of NBO/RGO ( R ct = 1.49 Ω), which suggests that the doping of Co elements can significantly promote charge transfer ( Figure 5F and Supplementary Figure S4D ). In addition, NCBO/RGO-3 has a nearly vertical Warburg angle as compared to CBO/RGO, indicating faster electrolyte ion diffusion within the NCBO/RGO-3 electrode ( Zhang et al, 2020 ). It also has been suggested that the M 3 (BO 3 ) 2 (M = Ni, Co) shell layer promotes the absorption of electrolyte OH − on the electrode surface ( Chen et al, 2019b ), and the abundant mesopores inside the NCBO/RGO-3 can facilitate the transport and infiltration of electrolyte ions within the whole electrode material.…”
Section: Resultsmentioning
confidence: 99%